The effect of organizational support and personality traits toward employees’ performance in frontline services in state government at Tangkak, Johor / Siti Aisyah Mohd Shuhaimi and Siti Nurnazirah Ahmad - Mohd Shuhaimi, Siti Aisyah; Ahmad, Siti Nurnazirah (Faculty of Business and Management, 2016)
The purpose of this study is to investigate the effect of organizational support and personality traits towards employees’ performance in frontline services. This study was conducted in government state in Tangkak District, Johor. The empirical part of this study was conducted in June 2016. Data for this study were obtained from questionnaire that distributed among employees in frontline service of government sector in Tangkak District. Ten government state company were selected for this investigation at Tangkak District. The questionnaire investigated how organizational support and personality traits of the employee can improve employees’ performance and respondents filled in a form by rated each item. Responses were made on a 5-point Likert scale ranging from one to five. The data obtained is be analyzed by Statistical Package from Social Science Version 23 (SPSSv23). Based on reliability test, respondent demographic, frequency, Pearson Correlation and Multiple Regressions, a clear findings and result is observed. The results showed that personality traits have a positive relationship with employee performance and the most dominant factor is intrinsic motivations that have the highest correlation with employee performance which means it contra from previous study. The researchers recommend to the organization to focus on personality traits of the employees to select a right person for a right job.